HOTS based Speaking and Reading Assessment in English Language Learning in Distance Learning System - Aliah, Nuraziza; Rohmah, Dewi Wardah Mazidatur; Hadianti, Siti; Jamilah, Sitti; Aisyah, Sitti (Anglophile Journal, 2023)
The article was to determine the Higher Order Thinking Skills (HOTS) based assessment in speaking and reading in English language learning in distance learning system. The method used qualitative research with a field study design. Collecting data through observation and interview. This research was conducted at SMA Muhammadiyah 4 Makassar with twenty English teachers. The results showed that the HOTS-based assessment in speaking and reading in English language learning within a distance learning system was carried out effectively by the English teachers. However, there were several challenges encountered during implementation, including technological limitations. Distance learning requires a stable internet connection and adequate devices, but not all students have good access to the internet, which can hinder teachers in effectively conducting speaking and reading assessments. Additionally, not all students have sufficient audio or video devices to participate in speaking assessments, which can hinder their ability to practice speaking clearly and listen well. Furthermore, there were challenges in providing direct and individual feedback in distance learning. In speaking assessments, timely and direct feedback is crucial for students to correct mistakes and improve their speaking skills. However, in distance learning, feedback was often given in written form or through recorded videos, which can result in delays and limit students' opportunities for improvement. Keywords: HOTS based Speaking, Reading Assessment, Distance Learning System